Collaboration with local tax authorities providing tax information - Majka, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Currently, there is an increasing cooperation in the exchange of tax information, and this information is also obtained from local tax authorities by other public administration bodies. The issue of providing tax information by local tax authorities is a part of a broader topic concerning the cooperation between administrative bodies. Collaboration between authorities in this regard brings about numerous challenges related to limiting the scope of information provision and the procedure in which it occurs. It is crucial to have legal mechanisms that ensure an efficient process of providing information while protecting the taxpayer’s rights. There is no doubt about the need to limit, for example, tax secrecy when disclosing information about taxpayers to other public authorities as part of their duties. Any intrusion into the right to privacy should be balanced with both the public interest and the taxpayer’s interest. The existing regulations regarding the subject matter of information provision by local tax authorities and the list of entities entitled to request this information are considered clear and not raising any doubts in their application. However, regarding the procedure for providing information and the form in which disclosure or refusal should take place, legislative changes are necessary, including the introduction of an obligation to inform the taxpayer about the disclosure of their information.

Współcześnie zwiększa się współpraca w zakresie wymiany informacji podatkowych, w tym informacje te pozyskiwane są również od samorządowych organów podatkowych przez inne organy administracji publicznej. Problem udostępniania informacji podatkowych przez samorządowe organy podatkowe stanowi przy tym wycinek szerszej problematyki współdziałania administracji. W związku ze współdziałaniem organów w tej dziedzinie pojawiają się liczne problemy związane z ograniczeniem zakresu udzielania informacji oraz procedury, w jakiej się ono odbywa. Jako istotne należy zatem uznać istnienie prawnych mechanizmów, które gwarantują sprawny tryb udzielania informacji oraz równocześnie chronią prawa podatnika. Nie budzi jednocześnie wątpliwości konieczność ograniczenia przykładowo tajemnicy skarbowej w sytuacji ujawniania informacji dotyczących podatników innym organom władzy publicznej w związku z wykonywaniem przez nie zadań. Ingerencji w prawo do prywatności towarzyszyć powinno zachowanie równowagi pomiędzy interesem publicznym oraz interesem podatnika. Obowiązujące regulacje w zakresie przedmiotu udostępniania informacji przez samorządowe organy podatkowy oraz katalog podmiotów uprawnionych do żądania tych informacji należy ocenić jako niewywołujące wątpliwości w ich stosowaniu. Z kolei w zakresie procedury udzielania informacji, form, w jakich udostępnienie lub odmowa powinny nastąpić, wskazano na konieczność zmian legislacyjnych, w tym wprowadzenia obowiązku informowania podatnika o ich udostępnianiu.
Współdziałanie z samorządowymi organami podatkowymi udostępniającymi informacje podatkowe
Keywords: tax information; cooperation between authorities; local tax authorities; tax secrecy; informacje podatkowe; współdziałanie organów; samorządowe organy podatkowe; tajemnica skarbowa